Mathematical Creative Thinking Ability in Term of Learning Independence in Creative Problem Solving Assisted Learning with Mobile Learning - Huda, Muhamad Nurul; Mulyono, Mulyono; Rosyida, Isnaini (Unnes Journal of Mathematics Education Research, 2021)
This study aims to describe the mathematical creative thinking ability in terms of students learning independence in learning Creative Problem Solving (CPS) assisted by mobile learning. The design of this study is squential explanatory. The population in this study was grade VIII of SMP Negeri 6 Salatiga consisting of eight classes. Determination of the subject grouped based on the learning independence of students with high, medium, and low categories using purposive. The results of the study show that Creative Problem Solving (CPS) learning assisted by mobile learning with certain quality because at the planning stage all devices are used valid, at the stage of implementing Creative Problem Solving (CPS) learning assisted by mobile learning in minimal good criteria, and at the assessment stage effective of Creative Problem Solving (CPS) assisted by mobile learning. Description of mathematical creative thinking ability in terms of learning independence of students varies. This is indicated by the following results; from 10 students with high learning independence obtained 2 people with mathematical creative thinking ability in the high category and 8 in the medium category. From 15 students with moderate learning independence, the results are obtained 1 person creative mathematical thinking ability in the high category and 13 people in the medium category and 1 person in the low category. The result of the research show that from 3 students with low learning independence, all are having low mathematical creative thinking skill.